Reconfiguration of radial electric power distribution system via a scatter search algorithm - Rupolo, D. [UNESP]; Mantovani, J. R. S. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2015)
In this paper, to solve the reconfiguration problem of radial distribution systems a scatter search, which is a metaheuristic-based algorithm, is proposed. In the codification process of this algorithm a structure called node-depth representation is used. It then, via the operators and from the electrical power system point of view, results finding only radial topologies. In order to show the effectiveness, usefulness, and the efficiency of the proposed method, a commonly used test system, 135-bus, and a practical system, a part of Sao Paulo state's distribution network, 7052 bus, are conducted. Results confirm the efficiency of the proposed algorithm that can find high quality solutions satisfying all the physical and operational constraints of the problem.
Keywords: Scatter search algorithm; Distribution power system reconfiguration; Exponential load model; Node-depth representation